IMPLEMENTASI PERADILAN ELEKTRONIK (E-COURT) PASCA DIUNDANGKANNYA PERMA NOMOR 3 TAHUN 2018 TENTANG ADMINISTRASI PERKARA DI PENGADILAN SECARA ELEKTRONIK - Hary Djatmiko (Universitas Muhammadiyah Kotabumi, 2019)
The continuous development of information and technology (IT), demands its adoption in court institutions worldwide. Therefore, the application of e-court in Indonesia started after the publication of Supreme Court Regulation number 3 of 2018. The purpose of this article is to describe the adaptation of the Indonesian Supreme Court to the use of information technology, in an effort to improve its performance. This research focuses on two research problems, firstly, how is the regulation and implementation of electronic court in Indonesia? Secondly, what are the implications of accessing its application among justice seekers? A normative approach, which relates the broad access towards the justice seeker, was used. The implementation of IT in court processes is a reformative initiative, through innovation, efficiency, structure and system. This advancement would also assist the judges in examining, judging and declaring a case. Socially, these further helps those who seek justice to cost effectively simplify and hasten the process, therefore mark a new era.